Back Cover: Triple‐Mode Emission of Carbon Dots: Applications for Advanced Anti‐Counterfeiting (Angew. Chem. Int. Ed. 25/2016). Issue 25 (6th May 2016) - Jiang, Kai; Zhang, Ling; Lu, Junfeng; Xu, Chunxiang; Cai, Congzhong; Lin, Hengwei
Abstract : Show me the money ! A printable ink with three modes of optical authentication could be used to combat counterfeiting. In their Communication onpage 7231 ff., H. Lin and co‐workers describe a carbon dot composite fixed in a PVA matrix with three modes of simultaneous emission; Chinese dragon boaters in various shades of blue depict photoluminescence (PL), up‐conversion PL (UCPL), and room temperature phosphorescence (RTP) emission by carbon dots.